Analisis Hubungan Antara Bangunan Bersejarah, Mitos, Budaya Masyarakat Lokal Dengan Motivasi Wisatawan Berkunjung Di Daya Tarik Wisata Tamansari Yogyakarta - Rahmat Abdullah; Tuti Panghastuti (STIE Pariwisata API Yogyakarta, 2018)
This study aims to determine the relationship between historic building variables, myths and cultures of local people to the motivation of visiting in the tourist attraction of Tamansari Castle Yogyakarta. The population in this study are tourists who visit the Castle tourist attraction in 2015. The sampling technique used is non probability sampling with accidental sampling method and sample size of 100 respondents. This research uses questionnaire as research instrument and data analysis technique used is descriptive and quantitative with Pearson correlation method. Result of research based on quantitative analysis indicate that historic building variables, myth and culture of local community have relation to motivation of tourists visiting in Tamansari. This can be shown from the result of correlation analysis where the sig value of the three variables is less than 0.05. based on the criteria, myths and cultural variables local communities have the relationship is with the tourist motivation, where the myth has a correlation coefficient of 0487 and 0481 local culture, the correlation value is in the interval 0.40 ≤ r <0.599. Whereas, for the variable historic building has a low correlation with tourist motivation with correlation coefficient 0.383, the correlation value is in the interval 0.20 ≤ r <0.399.